Entre Inri Cristo, crack e o amor - Gaioto, Alexandre (Acta Scientiarum. Language and Culture, 2014)
TREVISAN, Dalton. O anão e a ninfeta. Rio de Janeiro: Record, 2011. 159 p. ISBN 978-85-010-9479-7 850109479X